Synergistic Impact of Midlatitude Westerly and East Asian Summer Monsoon on Mid-Summer Precipitation in North China - Ke Shang; Xiaodong Liu; Xiaoning Xie; Yingying Sha; Xuan Zhao; Jiahuimin Liu; Anqi Wang (Atmosphere, 2025)
Midlatitude westerly and East Asian summer monsoon (EASM) are crucial circulation systems in the upper and lower troposphere of East Asia that significantly influence mid-summer precipitation pattern. However, their synergistic effect on mid-summer precipitation in North China (NC) remains unclear. In this study, the concurrent variations of mid-summer westerly and EASM are categorized into two configurations: strong westerly–strong EASM (SS) and weak westerly–weak EASM (WW). At the synoptic timescale, the SS configuration significantly enhances precipitation in NC, whereas the WW configuration suppresses mid-summer rainfall. The underlying mechanism is that the SS pattern stimulates an anomalous quasi-barotropic cyclone–anticyclone pair over the Mongolian Plateau–Yellow Sea region. Two anomalous water vapor channels (westerly-driven and EASM-driven water vapor transport) are established in the southern and western peripheries of this cyclone–anticyclone pair, ensuring abundant moisture supply over NC. Meanwhile, frequently occurring westerly jet cores in northern NC form a jet entrance region, favoring strong upper-level divergent pumping and deep accents in its southern flank. This synergy between strong westerlies and EASM enhances both the moisture transports and ascending movements, thereby increasing precipitation over NC. Conversely, the atmospheric circulation associated with the WW pattern exhibits opposite characteristics, resulting in decreased NC rainfall. Our findings elucidate the synoptic-scale influences of westerly–monsoon synergy on mid-summer rainfall, through regulating moisture transports and westerly jet-induced dynamic uplift, potentially improving predictive capabilities for mid-summer precipitation forecasting.